Toward a Semantic Theory of Universal NCIs - Yagi, Yusuke; Nakamura, Takanobu; Mizutani, Kenta (Proceedings of the Amsterdam Colloquium, 2024)
Negative Concord Items (NCIs) are quantificational expressions that must be licensed by a local negation. Though the licensing condition has often been characterized by syntactic terminologies, Kuhn (2022) pursued semantic characterization of the condition. This paper extends Kuhn’s analysis to NCIs with universal quantificational force, focusing on Japanese dare-mo. This is achieved by augmenting Hamblinian alternative semantics in Kuhn’s dynamic setup. The success of the analysis provides further support for merging dynamic semantics and alternative semantics.